Association of T2/S-RNase With Self-Incompatibility of Japanese Citrus Accessions Examined by Transcriptomic, Phylogenetic, and Genetic Approaches - Honsho, Chitose; Ushijima, Koichiro; Anraku, Misa; Ishimura, Shuji; Yu, Qibin; Gmitter, Frederick G.; Tetsumura, Takuya (Frontiers in Plant Science, 2021)
Several citrus varieties show gametophytic self-incompatibility (GSI), which can contribute to seedless fruit production in several cultivars. This study investigated the genes regulating this trait through RNA-seq performed using styles collected from the flowers of Japanese citrus cultivars, i.e., Hyuganatsu, Tosabuntan, Hassaku, Banpeiyu, and Sweet Spring. We screened the transcripts of putative T2 RNases, i.e., the protein family including all S-RNases from S-RNase-based GSI plants, and constructed a phylogenetic tree using the screened T2 RNases and S-RNases retrieved from citrus genome databases and a public database. Three major clusters (class I to III) were formed, among which, the class III cluster contained family specific subclusters formed by S-RNase and a citrus-specific cluster monophyletic to the S-RNase clusters. From the citrus class III cluster, six transcripts were consistent with the S haplotypes previously determined in Japanese citrus accessions, sharing characteristics such as isoelectric point, extracellular localization, molecular weight, intron number and position, and tissue-specific expression with S-RNases. One T2 RNase gene in self-incompatible Hyuganatsu was significantly down-regulated in the styles of a self-compatible mutant of Hyuganatsu in RNA-seq and qPCR analyses. In addition, the inheritance pattern of some T2 RNase genes was consistent with the pattern of the S haplotype in the progeny population of Hyuganatsu and Tosabuntan. As all results supported citrus self-incompatibility being based on S-RNase, we believe that six T2 RNase genes were S-RNases. The homology comparison between the six T2 RNases and S-RNases recently reported in Chinese citrus revealed that three out of six T2 RNases were identical to S-RNases from Chinese citrus. Thus, the other three T2 RNases were finally concluded to be novel citrus S-RNases involved in self-incompatibility.